Comparison between dual-energy X-ray absorptiometry and anthropometric predictive equations in assessing percentage body fat in soccer players with lower limb amputation - Cavedon, Valentina; Zancanaro, Carlo; Milanese, Chiara (Italian Journal of Anatomy and Embryology, 2018)
Anthropometric equations are an accessible and cost-effective method to assess percent- age body fat (%BF) in different athletic populations, but their reliability in athletes with limb amputation is unclear [1]. The aim of this study was to compare, in amputee soccer players, %BF estimated with several commonly used equations and dual-energy X-ray absorptiom- etry (DXA) taken as the reference method. Body density was assessed in 10 male soccer play- ers aged 33.9±11.9 years with transfemoral (n=7) or transtibial (n=3) lower limb amputation using five currently used anthropometric equations established for able-bodied subjects [Durnin and Womersley (1974), Jackson and Pollock 7-sites (1978), Sloan and Weir (1970), Wilmore and Behnke (1969), and Katch e McArdle (1973)]; body density was converted to %BF according to Siri (1961). %BF measured with DXA (Hologic) was used for assessing the validity of anthro- pometric equations (paired-sample t-test); the agreement between methods was assessed with the coefficient of determination and the standard error of estimate. Results showed that all the anthropometric equations significantly underestimate %BF (-2.7%÷-6.0 %; p, 0.012÷<0.001), but the Durnin and Womersley equation, which significantly overestimates %BF by +4.0%. The highest adjusted coefficient of determination was found for the Wilmore and Behnke equation (R2=0.805, p=0.001) and the lowest (R2=0.422, p=0.025) was found with the Durnin and Wom- ersley equation. The standard error of estimate ranged from 2.37% (Wilmore and Behnke equa- tion) to 4.08% (Durnin and Womersley equation). Further comparative studies are required to confirm or refine the accuracy of practical, non-invasive methods for monitoring %BF in the amputee athletic population. Impairment-specific equations may be needed in amputee soccer players with lower limb amputation.